Answer:p(x) = x^3 - 5x^2 - 4x + 20
Explanation:
1, - 1, 2, - 2, 4, - 4, 5, - 5, 10, - 10, 20, - 20
P(2) = 2^3 - 5 × 2^2 - 4 × 2 + 20
= 8 - 20 - 8 + 20 = 0,
so, 2 is one of its roots (zeros)
So,
x - 2 is one of the factors of p(x)
So, on dividing p(x) by x - 2 we get
P(x) = (x - 2) (x^2 - 3x - 10)
= (x - 2) (x^2 - 5x + 2x - 10)
= (x - 2) {x (x - 5) + 2 (x - 5)}
= (x - 2) {(x - 5) (x + 2)}
P(x) = (x - 5) (x - 2) (x + 2)
For zeros, let p(x) = 0
=> (x - 5) (x - 2) (x + 2) = 0
Either
(x - 5) = 0
Or
(x - 2) = 0
Or
(x + 2) = 0
So, x = 5, 2, - 2